A hybrid nanostructure-based electrochemical sensing strategy for the early diagnosis of basal stem rot - Fowotade, Sulayman Akanbi; Yusof, Nor Azah; Abdullah, Jaafar; Sulaiman, Yusran; Abd Rahman, Siti Fatimah (Royal Society of Chemistry, 2025)
This study aimed to improve the sensitivity of basal stem rot detection by using secondary metabolites as biomarkers in a biosensing strategy. A disposable and low-cost electrochemical platform was introduced using a screen-printed carbon electrode with a modified novel hybrid nanostructure containing gold nanoparticles, multiwalled carbon nanotubes, and chitosan nanoparticles.